Large-scale targeted sequencing identifies risk genes for neurodevelopmental disorders - Wang, Tianyun; Hoekzema, Kendra; Vecchio, Davide; Wu, Huidan; Sulovari, Arvis; Coe, Bradley P; Gillentine, Madelyn A; Wilfert, Amy B; Perez-Jurado, Luis A; Kvarnung, Malin; Sleyp, Yoeri; Earl, Rachel K; et al. (Nature communications, 2020)
Most genes associated with neurodevelopmental disorders (NDDs) were identified with an excess of de novo mutations (DNMs) but the significance in case-control mutation burden analysis is unestablished. Here, we sequence 63 genes in 16,294 NDD cases and an additional 62 genes in 6,211 NDD cases. By combining these with published data, we assess a total of 125 genes in over 16,000 NDD cases and compare the mutation burden to nonpsychiatric controls from ExAC. We identify 48 genes (25 newly reported) showing significant burden of ultra-rare (MAF < 0.01%) gene-disruptive mutations (FDR 5%), six of which reach family-wise error rate (FWER) significance (p < 1.25E-06). Among these 125 targeted genes, we also reevaluate DNM excess in 17,426 NDD trios with 6,499 new autism trios. We identify 90 genes enriched for DNMs (FDR 5%; e.g., GABRG2 and UIMC1); of which, 61 reach FWER significance (p < 3.64E-07; e.g., CASZ1). In addition to doubling the number of patients for many NDD risk genes, we present phenotype-genotype correlations for seven risk genes (CTCF, HNRNPU, KCNQ3, ZBTB18, TCF12, SPEN, and LEO1) based on this large-scale targeted sequencing effort.
Keywords: mutace; DNA vazebné proteiny; Basic Helix-Loop-Helix Transcription Factors; Female; CCCTC-vazebný faktor; Repressor Proteins; transkripční faktory; heterogenní jaderný ribonukleoprotein U; represorové proteiny; ženské pohlaví; mutační analýza DNA; High-Throughput Nucleotide Sequencing; transkripční faktory bHLH; proteiny vázající RNA; lidé; KCNQ3 Potassium Channel; draslíkový kanál KCNQ3; Transcription Factors; DNA Mutational Analysis; Mutation; genetická predispozice k nemoci; studie případů a kontrol; Genetic Predisposition to Disease; neurovývojové poruchy; kohortové studie; Cohort Studies; genetické asociační studie; Male; Case-Control Studies; vysoce účinné nukleotidové sekvenování; DNA-Binding Proteins; RNA-Binding Proteins; Neurodevelopmental Disorders; mužské pohlaví; CCCTC-Binding Factor; Heterogeneous-Nuclear Ribonucleoprotein U; Genetic Association Studies; Humans